PENGARUH WORK LIFE BALANCE DAN MANAJEMEN WAKTU TERHADAP PRESTASI AKADEMIK MAHASISWA YANG BEKERJA PARUH WAKTU (LITERATUR REVIEW) - Novalisa Firdausi Putri Hidayat; Cecep Hermana (Universitas Dharmawangsa, 2026)
Part-time working students face challenges in balancing academic and work responsibilities that can affect the academic achievement that will be achieved by students. This study aims to analyze the effect of work-life balance and time management skills on the academic achievement of students who work part-time. The research method used in writing this article is a literature review study, data collected through a study of several written sources in the form of journals and scientific articles to understand and disseminate existing knowledge on the topic. The findings of this study indicate that both work-life balance and time management have a significant positive effect on the academic performance of students who have dual roles as part-time workers.